Where is the (ancient) ocean floor? - Maric, Filip; Poto, Margherita; Panieri, Giuliana (Septentrio Educational, 2023)
Focus:To understand that that the ocean floor is dynamic and changes through time. Sometimes it’s far away, and sometimes much closer than we think. But where is the ocean floor?Learning objectives:In this activity, pupils will understand that we can find ancient ocean floors on land because of tectonic activity. NB: This will require prior planning and may not be possible if your school is too far from such tectonic formations.Key words:Sedimentation, sedimentary rocks, tectonics, Earth history.